A review: Issues and Challenges in Big Data from Analytic and Storage perspectives (International Journal of Engineering and Computer Science, 2017)
There is an up-and-coming topic in the field of computer science and technology that is getting a lot of publications these days and that is Big Data. The term Big data is referring for a collection of large and complex data sets which is very hard to process by database management tools or data processing applications. The volumes are in the range of Exabyte and above. Most of companies and government agencies are dealing with it in this current speedy moving technology environment. Stand -alone applications as well as today’s newer web-based processes are generating large amount of data. This raise some issues that has to be considered when dealing with big data. Some of the issues are storage, management and processing. This data also creates new challenges which make the framework based developers to come up with solutions to the problems. They introduced different frameworks for the storage, management and processing of big data that are scalable and portable with fault tolerance capabilities. Newer technologies for the analysis of such large amount data that is complex to handle are also introduced. These challenges include Privacy and Security, Scale, and Heterogeneity to mention a few. This paper reviews the Issues and Challenges of Big Data from Data Analytic and Storage Perspectives.We also briefly discussed about the frameworks and databases that can be used to tackle the challenges that is facing Big Data world.